2015
DOI: 10.1016/j.dsi.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric characteristics of systematic reviews in dermatology: A cross-sectional study through Web of Science and Scopus

Abstract: a b s t r a c tThe bibliometric characteristics of systematic reviews (SRs) in dermatology are unknown. We analyzed a group of 309 SRs using Scopus and the ISI Web of Science. These 309 SRs were published between 2008 and 2012 in journals with a median journal impact factor of 3.63; 48.2% (n ¼ 149) included metaanalysis, 11.6% (n ¼ 36) were Cochrane reviews, and 76.7% (n ¼ 237) summarized enough evidence to inform clinical decisions. The most common country of origin was the USA (n ¼ 66, 21.4%), and the most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“… 2 It is critical now more than ever to ensure reviews are sufficiently reported, given the continual increase in systematic reviews within dermatology. 3 Reviews that are well reported allow clinicians and policy makers alike to make transparent and informed judgments to guide decisions within dermatology. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement is a 27-item checklist that ensures reporting transparency of a review.…”
Section: Introductionmentioning
confidence: 99%
“… 2 It is critical now more than ever to ensure reviews are sufficiently reported, given the continual increase in systematic reviews within dermatology. 3 Reviews that are well reported allow clinicians and policy makers alike to make transparent and informed judgments to guide decisions within dermatology. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement is a 27-item checklist that ensures reporting transparency of a review.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis is a method that has been increasingly used in many areas of knowledge [15]. It presents advantages over the traditional literature review, as it provides a more objective and systematic selection and assessment of scientific research in a given field [13,[16][17][18]. Bibliometry is the most appropriate methodology to identify the state-ofthe-art of literature or, as Teixeira (2014) [19] puts it, the "leading edge" of a research field.…”
Section: Methodsmentioning
confidence: 99%
“…Given the increase in systematic reviews within dermatology it is important, perhaps now more than ever, to ensure reviews are adequately reported [7]. Well-reported reviews will ensure clinicians and policy makers alike are able to make complete and transparent judgments to guide key healthcare decisions and ensure cost-effectiveness of treatments within dermatology.…”
Section: Introductionmentioning
confidence: 99%